Kritik Atas Fenomena Inkonsistensi Beriman Mahasiswa Manggarai Di Malang Perspektif Budaya Tanding (Roma 12:2) - Rabim, David (Jurnal Masalah Pastoral, 2023)
The focus of this research is criticism of the phenomenon of inconsistency in the faith of Manggarai students in Malang based on Romans 12:2. Two factors cause inconsistency of faith, namely the shock culture and the lack of critical function over the development of the times. Shock culture can be seen in the cultural differences between rural communities (the original culture of students) which emphasize aspects of social control and urban communities which inherit an individualistic and hedonic spirit of life. This difference also affects the way they live their faith. Faith that grows and is educated in a culture of social control does not bear fruit when living in an individualistic and hedonic culture. For this phenomenon, the author places the apostle Paul's letter to the congregation in Romans 12:2 as the lens of his criticism. Paul emphasizes two important things namely "do not be conformed to this world and change with the renewal of the mind". Students are required to revive the spirit of repentance, namely to renew themselves and reject all forms of worldly tendencies.